Effects of wetting layer on exciton binding energy of strained CdTe/ZnTe pyramidal quantum dots. (February 2015) - Park, Seoung-Hwan; Hong, Woo-Pyo; Kim, Jong-Jae; Ahn, Doyeol
Abstract: Effects of wetting layer on exciton binding energy of strained Cd1− x Zn x Te/ZnTe pyramidal quantum-dots (QDs) are theoretically studied by using an eight-band strain-dependent k · p Hamiltonian. We find that exciton binding energies significantly depend on the wetting layer thickness. That is, the QD with smaller wetting layer thickness shows much larger exciton binding energies than that with larger wetting layer thickness because of the increase in the carrier confinement effect. Also, the exciton binding energies for the QD with a larger Zn composition are shown to be slightly smaller than those with a smaller Zn composition. This is attributed to the decrease in the carrier confinement due to the reduced band gap. Abstract : Highlights: The exciton binding energies of pyramidal QDs significantly depend on the wetting layer thickness. The exciton binding energies for the QD depend on the Zn composition. The present work is expected to be useful for a design of QD structures.